Long-term efficacy data for the recombinant zoster vaccine: impact on public health and cost effectiveness in Germany - Desmond Curran; Desirée Van Oorschot; Sean Matthews; Johannes Hain; Ahmed Ehab Salem; Magdalena Schwarz (Taylor & Francis Group, 2021)
The aim of the study was to update previously published public health impact and cost-effectiveness analyses of the recombinant zoster vaccine (RZV), in the German population aged ≥50 years of age (YOA), with the latest vaccine efficacy (VE) estimates against herpes zoster (HZ). The updated estimates are derived from a long-term follow-up study. A previously published multi-cohort Markov model following age cohorts over their lifetime was used. Demographic, epidemiological, cost, and utility data were based on German specific sources. Vaccine coverage was assumed to be 40%, with a second dose compliance of 70%. The estimated VE at time 0 was 98.9% (95% C.I.: 94.0-100%) with an annual waning of 1.5% (95% CI: 0.0-3.4%) for the age group 50-69 YOA. Corresponding values were 95.4% (95% C.I.: 89.7-100%) and 2.3% (95% CI: 0.3-4.4%) for the age group ≥70 YOA. It was estimated that, over the remaining lifetime since vaccination, RZV would prevent approximately 884 thousand (K), 603 K, and 538 K HZ cases in three age cohorts 50-59, 60-69, and ≥70 YOA, respectively. The number needed to vaccinate to prevent one HZ and one postherpetic neuralgia case was 6 and 36 (50-59 YOA cohort), 6 and 34 (60-69 YOA cohort), 10 and 48 (≥70 YOA cohort). The incremental cost-effectiveness ratio of vaccination ranged from €26 K/quality-adjusted life year (QALY) in 60 YOA to €35 K/QALY in 70 YOA. Due to the higher, sustained, RZV VE, improved public health and cost-effectiveness results were observed compared to previous analyses.